Reflections of Today’s Teens Behavior: From Impressions on Social Media to Cognitive Dissonance - Rustono Farady Marta; Miletresia; Maristela Fernandes (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2022)
Social media has been used as a form of user character in Cyberspace. The new form of new media that was originally used as a place of self-expression has now built the users’ behavior. The used for representing themselves on social media initially aims to give an impression to other users then occur a cognitive dissonance behavior between behavior in the real world and things uploaded on social media. By using qualitative methods which focus on equilibrium in Tzvetan Todorov’s narrative analysis, researchers want to see the contrast in the behavior of social media users through the film ‘Social Life’. The author uses Impression Management Theory and Cognitive Dissonance Theory to describe and at the same time interpret the impression that the characters want to build in the film as well as the cognitive dissonance of social media users' behavior through the interpretation of the short film ‘Social Life’. The implication of this research is in the form of a narrative plot that shows the uncomfortable situation of the main character (Meredith) due to her desire to display a different self-image on social media so that this cognitive dissonance becomes the main consideration for leaving her social life.